MEMBANGUN METODOLOGI PENELITIAN SEJARAH UNTUK PENGEMBANGAN ISLAMIC STUDIES - Syamsul Bakri; Dinar Bela Ayu Naj'ma (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Historical studies are a vital discussion in various social sciences and humanities, including Islamic studies. Islam and Muslims are not static entities, but a continuous fact. In Islamic studies, a historical approach has actually been carried out, not only in relation to the chronology of Islamic development. This research uses descriptive qualitative research methods. The data were taken from historical science literature, then analyzed by theoretical hermeneutics which were then analyzed using the triangulation method, namely by conducting a cross check between theories in the historical method. The results of this research show that there are aspects of Islamic history that must be understood objectively so as not to lose the orientation of space and time, so that all doctrines, schools of thought and civilization in Islam can be presented objectively.Keywords:Â History;Â Methodology; Islamic Studies.